Moustache restoration using follicular unit extraction technique for esthetic repair of prolabial alopecia in adult male patients with repaired bilateral cleft lip: An initial report in eight patients - Sunil Richardson; Rakshit Khandeparker; Shreya Krishna (Wolters Kluwer Medknow Publications, 2018)
Prolabial alopecia is an inherent feature of bilateral cleft lip cases, occurring in varying degrees which is worsened following cleft lip repair. In the Southeast Asian population, a strong healthy moustache is considered a symbol of pride and hence many patients seek treatment of their alopetic prolabium due to the cleft lip. The alopetic prolabium also adds to the patients dented confidence by adding to the typical cleft lip look. Among the two techniques mentioned in the literature for hair restoration, namely, follicular unit extraction (FUE) and follicular unit transplantation techniques, the FUE technique offers a minimally invasive and virtually scar less option and is often preferred by most of the patients as well as the surgeons. A very few studies have focused on moustache restoration in adult male patients presenting with prolabial alopecia following bilateral cleft lip repair. This article presents the initial report in 8 adult male patients presenting with prolabial alopecia after repaired bilateral cleft lip that underwent moustache restoration using the FUE technique of hair restoration.